PENGARUH PENGGANTIAN SEBAGIAN RANSUM KOMERSIL DENGAN TEPUNG MAGGOT (Hermatia illucens) TERHADAP ORGAN DALAM AYAM BROILER - Dwi Bayu; Yeni Karmila; Bopalyon Pedi Utama (STOCK Peternakan, 2022)
This study aims to determine the effect of giving maggot flour to the internal organs of broiler chickens. This research was carried out on the street. Kenari RT 04 Sapta Mulya Village, Rimbo Bujang District, Tebo Regency for 35 days from 29 March - 27 April 2022. The experimental design used was a completely randomized design (CRD) with 5 treatments and 4 replications, where there were 5 DOCs in each unit. Each treatment was given a ration, namely M0 (100% commercial ration), M1 (5% maggot flour + 30% fine bran + 65% commercial ration), M2 (10% maggot flour + 30% fine bran + 60% commercial ration) , M3 (15% maggot flour + 30% fine bran + 55% commercial ration), M4 (20% maggot flour + 30% fine bran + 50% commercial ration). Parameters observed were liver weight percentage, proventriculus weight percentage, ventricular weight percentage, and small intestine weight percentage. Using the DNMRT test, if it has a significant effect on all observed parameters, the maggot flour used in this study reaches a level of 20%. The results of this study can be concluded that substituting commercial rations with maggot flour up to a level of 20% has no significant effect on liver weight percentage, proventriculus weight percentage, and small intestine weight percentage. But it has a real effect on the weight of the ventricles